2017
DOI: 10.2136/vzj2016.06.0049
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Micro‐CT: How Soil Pore Space Description Can Be Altered by Image Processing

Abstract: A physically accurate conversion of the X-ray tomographic reconstructions of soil into pore networks requires a certain number of image processing steps. An important and much discussed issue in this field relates to segmentation, or distinguishing the pores from the solid, but pre-and post-segmentation noise reduction also affects the pore networks that are extracted. We used 15 two-dimensional simulated grayscale images to quantify the performance of three segmentation algorithms. These simulated images made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 58 publications
1
16
0
2
Order By: Relevance
“…Although a large number of thresholding methods have been developed for segmentation of X‐ray CT image of soils, none of theoretical ‘standards' is generally accepted at present (Baveye et al, ; Iassonov et al, ; Marcelino et al, ; Smet et al, ; Taina I a, Heck RJ, Elliot TR., ; Wang et al, ). Due to the uncertain influences, such as unique characteristics of collected samples, resolution size of images, selection of thresholding algorithms, and unpredictable observer behavior, in the process of image segmentation, the previous studies often suggested different strategies for image segmentation after comparing various thresholding methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a large number of thresholding methods have been developed for segmentation of X‐ray CT image of soils, none of theoretical ‘standards' is generally accepted at present (Baveye et al, ; Iassonov et al, ; Marcelino et al, ; Smet et al, ; Taina I a, Heck RJ, Elliot TR., ; Wang et al, ). Due to the uncertain influences, such as unique characteristics of collected samples, resolution size of images, selection of thresholding algorithms, and unpredictable observer behavior, in the process of image segmentation, the previous studies often suggested different strategies for image segmentation after comparing various thresholding methods.…”
Section: Discussionmentioning
confidence: 99%
“…Previous review articles and research papers have offered sufficient study cases in exploring the reliability of applying X‐ray CT to quantify the soil pore characteristics (Cnudde & Boone, ; Haeffneff, ; Naveed et al, ; Taina et al ., 2008; Zhou, Mooney, & Peng, ). For example, studies have been widely carried out on segmentation of X‐ray CT images (Baveye et al, ; Iassonov, Gebrenegus, & Tuller, ; Schlüter, Sheppard, Brown, & Wildenschild, ) involving image resolution selection (Sleutel et al, ; Wildenschild et al, ), representative elementary area identification (San José Martínez, Caniego, García‐Gutiérrez, & Espejo, ), and optimal thresholding methods (Elliot & Heck, ; Smet, Plougonven, Leonard, Degré, & Beckers, ; Wang, Kravchenko, Smucker, & Rivers, ); quantification and reconstruction of the pore structure (Marcelino, Cnudde, Vansteelandt, & Carò, ) such as characterization of macropores (Garbout, Munkholm, & Hansen, ; Luo, Lin, & Schmidt, ), extraction of three‐dimensional (3D) typical pore parameters (Al‐Raoush & Willson, ; Luo, Lin, & Li, ), and assessing the spatial variability of soil structure (Carducci, Zinn, Rossoni, Heck, & Oliveira, ); as well as the relationship between pore characteristics and soil functions (Helliwell et al, ) including correlations with soil physical properties (Anderson, Gantzer, Boone, & Tully, ; Munkholm, Heck, & Deen, ) and explanation of the hydraulic conductivity (Luo, Lin, & Halleck, ; Naveed et al, ; Paradelo et al, ; Tracy et al, ). Although the majority of current case studies focus on naturally cultivated soils, there are still some reports confirming that images extracted from X‐ray CT are effective in quantifying pore characteristics of unnaturally soils such as reconstructed, degraded, and reclaimed soils (Dowuona, Taina, & Heck, ; Langmaack, Schrader, Rapp‐Bernhardt, & Kotzke, ; Li, Shao, & Jia, ; Wang, Guo, Bai, & Yang, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the impact on PSD is usually neglected in soil amendment experiments because it is difficult to quantify by classical field/laboratory methods, including direct or indirect measurement of PSD from water retention curve (WRC) measurements based on soil water content or geophysical measurements and hydrological inversion (as done by Jadoon et al, 2012; Busch et al, 2013; and Jonard et al, 2015) or WRC measured by pressure plate extractors (e.g., Bittelli and Flury, 2009); multistep outflow (e.g., Bayer et al, 2005; Hollenbeck and Jensen, 1998; Neyshabouri et al, 2013; Weihermüller et al, 2009); or the evaporation (e.g., Schindler et al, 2010; Žydelis et al, 2018), mercury intrusion (e.g., Webb, 2001), and nitrogen sorption (e.g., Kowalczyk et al, 2003) methods. As an alternative, noninvasive measurement techniques can be used, such as MicroCT (e.g., Koestel, 2018; Pohlmeier et al, 2018; Smet et al, 2017), synchrotron radiation and/or microtomography (e.g., Peth et al, 2008), or nuclear magnetic resonance relaxometry (NMRR) (e.g., Jaeger et al, 2009; Stingaciu et al, 2010).…”
mentioning
confidence: 99%
“…The study of the impact on PSD is usually neglected in soil amendment experiments because it is difficult to quantify by classical field/laboratory methods, including direct or indirect measurement of PSD from water retention curve (WRC) measurements based on soil water content or geophysical measurements and hydrological inversion (as done by Jadoon et al, 2012;Busch et al, 2013;and Jonard et al, 2015) or WRC measured by pressure plate extractors (e.g., Bittelli and Flury, 2009); multistep outflow (e.g., Bayer et al, 2005;Hollenbeck and Jensen, 1998;Neyshabouri et al, 2013;Weihermüller et al, 2009); or the evaporation (e.g., Schindler et al, 2010;Žydelis et al, 2018), mercury intrusion (e.g., Webb, 2001), and nitrogen sorption (e.g., Kowalczyk et al, 2003) methods. As an alternative, noninvasive measurement techniques can be used, such as MicroCT (e.g., Koestel, 2018;Pohlmeier et al, 2018;Smet et al, 2017), synchrotron radiation and/or microtomography (e.g., Peth et al, 2008), or nuclear magnetic resonance relaxometry (NMRR) (e.g., Jaeger et al, 2009;Stingaciu et al, 2010).…”
mentioning
confidence: 99%